PERENCANAAN BISNIS MERCHANDISE RESMI UNIVERISTAS ABC DENGAN MENGGUNAKAN TIMMONS MODEL - Annisa Maharani Suyono; Obsatar Sinaga; Tezza Adriansyah Anwar (Jurnal Ilmiah Teknologi Infomasi Terapan, 2019)
Company image is important because it influences consumer decisions in buying products. Similarly, in universities which are institutions where universities look for students, like companies that look for consumers. One of the university's appeals that can be done is through merchandise. In this case, ABC University plans to establish an official merchandise store as an effort to create a brand mind or incorporate a campus brand into every heart of people who see and also raise everyone's curiosity about ABC University. At present, the target market reaches 11,485 people, consisting of 96% students and 4% lecturers and employees. This amount represents a high enough market opportunity for ABC University official merchandise stores. This study uses a semi-structured interview data collection technique with the founding and managing team as well as documentation by collecting available internal company data relating to the merchandise shop. In this study, business feasibility will be carried out using the entrepreneurial criteria according to Timmons. In theory, the Timmons Model can be used as a guide to achieving success in entrepreneurship by taking into account opportunities, resources and team factors. Business positions according to the results of EFAS (0.93) and IFAS (0.79) are in quadrant I which supports an aggressive strategy. The official merchandise shop business is feasible and includes high-potential business conditions to be implemented and developed according to the results of Timmons' quick screen criteria. The results of the calculation of financial projections that obtain high potential categories, namely, IRR of 84%, Gross Profit Margin by 32%, Net Profit Margin by 20% and ROI by 48%.